IMPROVING THE SYSTEM OF COST ACCOUNTING AND ITS STRATEGIC ANALYSIS IN BANKS - Saparov Jasurbek Bobojonovich; Kahharov Zuhriddin Zafarbek o’g’li (The Conference Hub, 2025)
Ensuring the competitiveness and financial stability of commercial banks largely depends on the efficient use of their internal resources. In particular, the proper accounting, analysis, and strategic use of cost information are among the essential conditions for effective bank management. The data on costs generated within the framework of accounting serve as a crucial information base for assessing the profitability of banking activities, determining the profitability of specific services, and ensuring the efficient allocation of resources. Therefore, the proper organization of cost accounting and its transformation into a tool for strategic management is considered a pressing issue in modern banking practice.